Learning Profile of Narrative Text Reading Comprehension Using DRTA Strategy in Seventh Grade Students (Scripta : English Department Journal, 2026)
Reading comprehension at SMP Negeri 1 Nanggulan remains critically low, with an average score of 58.3 against a minimum standard of 75. This reflects a substantial gap between current instructional methods and student needs. This study details the actual learning profile of narrative text reading comprehension and analyzes the need for implementing the Directed Reading Thinking Activity (DRTA) strategy among seventh-grade students. Using a qualitative descriptive approach, the research involved 30 students and 2 Indonesian Language teachers, with data collected through interviews, observations, and document analysis, analyzed through Miles and Huberman's model. The findings show that existing teaching modules rely solely on a single narrative textbook, without involving process guidance, print-only media, and literal assessment. Classroom instruction lacks strategic reading phases, and teachers face limited training, time constraints, and a lack of DRTA-based materials. Needs analysis indicates that most students struggle with inferential comprehension, few have received structured reading-strategy instruction, and nearly all strongly require DRTA-based instructional materials. The pronounced gap between existing conditions and student needs underscores the immediate necessity for DRTA-based narrative reading comprehension materials.